Aesthetic order : a philosophy of order, beauty and art - Lorand, Ruth (Routledge studies in twentieth century philosophy., 2000)
"The book begins with a detailed discussion of the notions of order, disorder, and their mutual dependence. It proceeds with an analysis of interpretation. The notion of aesthetic order is presented as a complementary notion to the traditional, discursive concept of order, which is quantitative in its approach. Aesthetic order, as both quantitative and qualitative, interprets experience and expresses values, cultural and individual preferences, and a sense of necessity. Lorand draws from an impressive breadth of philosophical material from Plato to Spinoza, Kant, and Wittgenstein, as well as contemporary aestheticians such as Goodman, Mothersill, Ingarden, Danto, Margolis, and others. She also draws from recent research in experimental aesthetics and Information Theory." "Aesthetic Order challenges contemporary theories of aesthetics, offering beauty as a form of interpretation that integrates both quantitative and qualitative aspects of experience. It will be of importance to anyone interested in aesthetic theory."--Jacket